VoIP performance management and optimization - Ahmed, Adeel; Madani, Habib, 1969-; Siddiqui, Talal, 1973- (Indianapolis, Ind. : Cisco Press, 2011)
A comprehensive expert guide to managing, monitoring, troubleshooting, and optimizing large VoIP networks.
Includes Index
rua 30/10/13
Loans
Keywords: Internet telephony -- Management; Computer network protocols